2009
DOI: 10.1016/j.jda.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Eulerian orientations of triangular lattice graphs

Abstract: We consider the problem of sampling from the uniform distribution on the set of Eulerian orientations of subgraphs of the triangular lattice. Although Mihail and Winkler (1989) showed that this can be achieved in polynomial time for any graph, the algorithm studied here is more natural in the context of planar Eulerian graphs. We analyse the mixing time of a Markov chain on the Eulerian orientations of a planar graph which moves between orientations by reversing the edges of directed faces. Using path coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Not surprisingly, counting α-orientations is #P -complete. Namely, consider an undirected Eulerian graph G (with all even degrees); the α-orientations of G, where α(v) = d(v)/2, correspond precisely to Eulerian orientations of G. The latter problem has been shown to be #P -complete by Mihail and Winkler [22], and more recently Creed [8] showed that it remains #P -complete even when restricted to the class of planar graphs.…”
Section: -Orientationsmentioning
confidence: 99%
“…Not surprisingly, counting α-orientations is #P -complete. Namely, consider an undirected Eulerian graph G (with all even degrees); the α-orientations of G, where α(v) = d(v)/2, correspond precisely to Eulerian orientations of G. The latter problem has been shown to be #P -complete by Mihail and Winkler [22], and more recently Creed [8] showed that it remains #P -complete even when restricted to the class of planar graphs.…”
Section: -Orientationsmentioning
confidence: 99%
“…The results of this paper have recently been used to show rapid mixing of a Markov chain on the set of Eulerian orientations of a triangular subsection G of the triangular lattice [4]. The Markov chain M o used is as follows.…”
Section: Application: Sampling Eulerian Orientations Of the Triangulamentioning
confidence: 99%
“…The additional moves allowed in M o involve reversing the edges bounding several adjacent faces with some probability, in the event that the face selected at random does not form a directed cycle. In [4] it is shown that β( M o ) 1. An appeal to Theorem 2 of this paper completes the proof of rapid mixing, avoiding an involved direct proof bounding σ 2 ( M o ).…”
Section: Application: Sampling Eulerian Orientations Of the Triangulamentioning
confidence: 99%
See 2 more Smart Citations